Profil Asam Amino Ekstrak Mukus Ikan Glodok (Boleophthalmus boddarti) dari Kawasan Mangrove Cilacap, Jawa Tengah - Riviani Riviani; Dewi Wisudyanti; Iqbal Ali Husni (Jurnal FishtecH, 2020)
Mudskipper or glodok fish is a unique fish that can crawl and climb mangrove roots with their fins. In Indonesia, this fish is exported to abroad as a source of food. The by-product of this fish is rarely used, which one is their mucus. Protein is a composition of fish mucus which consists of  amino acids. The mucus of fish has the potential as a source of medicine because it’s proven to have antibacterial, antiviral, and antifungal activities. This study aims to determine the protein and amino acid content of fresh meat and mucus extract of mudskipper. Protein content testing was carried out using the titrimetric method, while amino acid content using the UPLC method. In this study, mucus extract has protein content at 1.79%. It’s small than the protein content of fresh meat at 17.7%. The highest essential amino acid in fresh meat and mucus extract of mudskipper was leucine (15% and 0.91%). The highest nonessential amino acid in fresh meat and mucus extract of mudskipper were glutamic acid (26.4% and 1.6%). The limiting amino acid in fresh meat is leucine as 226.9% and lysine as 12.27% in the mucus extract of mudskipper.